‘Benchmarking’ a Supreme Court and Federal Court judge in Australia - Francesca Bartlett; Heather Douglas (Oñati Socio-Legal Series)
In this article, we reflect upon the backgrounds and career trajectories of judicial officers currently presiding over the Federal Court and Supreme Courts, which are some of the highest courts, in Australia. We gathered information through publicly available websites in Australia providing official biographical information, and drew on academic efforts to fill in more details about the judiciary. While patchy, the picture today in the Australian judiciary is of a relatively uniform educational and career background – for both male and female judges. Our analysis shows that judges are predominantly recruited from a long career at the private Bar. However, given continued professional barriers to women succeeding in the Australian legal profession which we describe, we argue that it is time to take seriously the stated goals of modern judicial appointment to widen the pool and consider merit that is not solely defined by a benchmark male career.